THE SIGNIFICANCE OF ALLEGORY AND IRONY IN LANGUAGE ACQUISITION AND COMPREHENSION (American Journal of Research in Humanities and Social Sciences, 2023)
This article explores the significant impact of allegory on language comprehension focusing on the way of engaging the reader's cognitive processes, fostering critical thinking, and encouraging deeper understanding of complex concepts. The article investigates irony in satire that serves as a powerful tool for social commentary. It allows satirists to critique and ridicule individuals, institutions, or society while engaging and entertaining the audience. By using irony, satirists provoke thought and reflection, ultimately contributing to a more critical and aware society.